The Transformation of Corporate ControlThe Transformation of Corporate Control, by Fligstein Neil, Cambridge, MA: Harvard University Press, 1990, 391 pp., $35.00, cloth. - Kreiner, Peter (Academy of Management Review, 1991)
This article presents a review of the book ?The Transformation of Corporate Control,? by Neil Fligstein.